2017
DOI: 10.1200/jop.2017.021303
|View full text |Cite
|
Sign up to set email alerts
|

Informed Consent and Decision Making Among Participants in Novel-Design Phase I Oncology Trials

Abstract: Novel phase I oncology trial designs may attract patients with less constrained treatment options, but the inclusion of targeted drugs and combinations including standard chemotherapies is likely to complicate understanding of safety and dosing objectives and likelihood of personal benefit for purposes of informed consent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
57
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(58 citation statements)
references
References 30 publications
1
57
0
Order By: Relevance
“…The trusting relationship between patient and professional meant that all consenting patients felt their doctor saw the clinical trial as the best treatment for them as an individual. This finding is consistent with other studies [11,25,40] which have identified trust as a central component to trial decision-making. Findings in our study clearly showed that doctors were aware that patients trusted them and felt burdened by this, though were perhaps not aware of the power they had to influence patients' decision making.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The trusting relationship between patient and professional meant that all consenting patients felt their doctor saw the clinical trial as the best treatment for them as an individual. This finding is consistent with other studies [11,25,40] which have identified trust as a central component to trial decision-making. Findings in our study clearly showed that doctors were aware that patients trusted them and felt burdened by this, though were perhaps not aware of the power they had to influence patients' decision making.…”
Section: Discussionsupporting
confidence: 93%
“…The quality and validity of informed consent is critical, but previous research asserts that understanding can be limited and patients often confuse trial care with standard care [9][10][11][12]. Many factors have been identified as impacting on patients' understanding, such as literacy [13], readability, complexity of consent forms and quality of explanations by the research team [14].…”
Section: Introductionmentioning
confidence: 99%
“…Unexpected and unrealistic views of patients on adverse effects of systemic treatment and surgical complications can result in decreased confidence in medical care, negative coping, and a deterioration in quality of life. It is well-known from phase I trials, that patients underestimate the potential toxicities that could result from oncological therapy (66). To improve awareness, recent efforts have focused on incorporating online information tools in oncology care.…”
Section: Discussionmentioning
confidence: 99%
“…Any uncertainty of benefit, likely adverse effects, and estimated prognosis should be clearly communicated and understood by the patients before any decisions are made for proceeding to treatment. [ 9 ] Hence, it is not just a question of clinical effectiveness, but of balancing the potential benefits and harms of different available options to find what is most appropriate for the individual, and sometimes clinical practice guidelines not that effective in communication with patients. [ 10 ]…”
Section: R Esultsmentioning
confidence: 99%